Peningkatan Keterampilan Menyimak Intensif Siswa Kelas V SD Negeri 24 Palembang melalui Pendekatan PAKEM Berbahan Cerita Anak - Putri Mindari (Prosiding Seminar Nasional Jurusan PGSD FIP UNP Tahun 2015, 2015)
This research was aim at improving the intensive listening skill students at fifth grade of State Primary School 24 Palembang through PAKEM approach by using children stories. The method used is classroom action research. Data were collected by using intensive listening skills test dan observasion of student learning activity. The results obtained in the first cycle was 31.81% at mastery learning with the average value of 54.86 intensive listening skills. In the second cycle, results obtained at mastery learning 62.50% with the average value of 65.75. In the third cycle, mastery learning acquired 91.67% with an average value of 78.54. The progress of students mastery learning are also supported by the percentage of student activity. In the first cycle, student activity is obtained 53.90%, it improved 64.84% in second cycle. At third cycle, students' activity has reached 80.20%. Based on the results obtained, it can be concluded that PAKEM approach through children story can improve students of fifth grade of students at State Primary School 24 in Palembang in intensive listening skills and their activity in learning